Coping with flap and actuator driving constraints in active rotor applications for vibration reduction - Morales, R.M.; Turner, M.C. (My University, 2015)
Among the various approaches to mitigate vibration, On-Blade Control (OBC) embeds actuation mechanisms on the blade in order to modify the vibratory loads at the source and achieve improved vibration reduction than conventional Higher Harmonic Control. Recent OBC studies have applied constrained optimisation methods to the design of vibration control algorithms to compensate against the effects of limited actuation and hence avoid significant performance degradation. These recent studies do not consider however constraints on the driving signals of the actuators. Such limitations can also have a significant and negative impact in the overall performance. For this, anti-windup control strategies are implemented to compensate against such actuator limitations. This work combines for the first time both actuator constraint handling methods for OBC applications and tested on a simplified model of a five-blade rotor with Active Trailing Edge Flaps. Performance results exhibit an improvement of almost a factor of 2 with respect to not using any constraint handling method.
Keywords: Dynamics